FAIR VALUE RECOGNITION – POLISH ACCOUNTANTS PERSPECTIVE - Luty, Piotr; Piotrowska, Katarzyna; Kaczmarczyk, Angelika (The European Journal of Applied Economics, 2024)
The paper aims to explore the attitude of accountants to fair value measurements. The sample consists of Polish accountants with various working places and practical experiences. The authors assumed no difference in fair value recommendations between accountants. The authors considered a difference in the practical use of fair value models in accountants with more extended experience and the workplace. The method of analysis of sources (literature), deductive reasoning and survey research were used. The study used a questionnaire addressed to Polish accountants. The results confirmed that most accountants, regardless of gender, working place or length of experience, recommended a fair value method for improving the credibility of financial figures. Despite the recommendation, more experienced accountants and accountants working in accounting offices mostly use historical cost methods instead of fair value methods. The main restriction concerns that the quantitative study was preliminary and refers only to Polish accountants. The article fills the research gap in preferable valuation methods regarding the gender of the person responsible for accounting.
Keywords: fair value, accountant, gender; fer vrednost, računovodstvo, pol